THE EFFECT OF INTRINSIC MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT CV. SUGIH KOTA SIBOLGA - Arifman Hakim; Mansur Tanjung; Riwayani Riwayani; Lukman Hakim Hutagalung (Universitas Dharmawangsa Medan, 2026)
This study aims to determine the effect of intrinsic motivation and job satisfaction on employee performance at CV. Sugih Kota Sibolga. The background of this study is based on the importance of human resources as a key asset of the company, especially in the fisheries sector, which requires employees to have high work enthusiasm and job satisfaction. This study uses a quantitative approach with a comparative causal method. The sample in this study consisted of 38 employees, selected using total sampling technique. The data collection instrument was a questionnaire compiled based on indicators from each variable. The data analysis technique used was multiple linear regression analysis using SPSS software. The results showed that intrinsic motivation had a positive and significant effect on employee performance, as indicated by a significance value of 0.032 (< 0.05). Similarly, job satisfaction also has a positive and significant effect on employee performance, with a significance value of 0.019 (< 0.05). Simultaneously, intrinsic motivation and job satisfaction have a significant effect on employee performance with a coefficient of determination (R²) value of 0.370. This is also supported by the F test results, which show a significance value of 0.001 (< 0.05), so that the regression model as a whole is suitable for predicting employee performance, while the hypothesis results are that intrinsic motivation and job satisfaction simultaneously have a significant effect on employee performance.Keywords: Intrinsic motivation; job satisfaction; employee performance; CV. Sugih Kota Sibolga